Apneic laryngeal chemoreflex and naloxone (Revista Española de Fisiología, 1986)
The apneic laryngeal chemoreflex (QRL), elicited by water on the vocal cords and by mechanical stimulation (MRL) has been compared in dog.Both stimuli cause apnea, bradycardia, hypotension and constriction of the glottis.In QRL apnea predominates white in MRL bradycardia is more intense.All the components of the response decrease with naloxone at a 400 micrograms X kg-1 doses, suggesting that the reflex inhibition depends on endogenous opioids located in the respiratory centre.